MARRIAGE AGREEMENTS AND ASSET CONFISCATION IN MONEY LAUNDERING: INDONESIAN COURT ANALYSIS - Usanti, Trisadini Prasastinah; Aryatie, Indira Retno; Limantara, Vanessa Widya (YURIS: Journal of Court and Justice, 2025)
This study examines the legal position of marriage agreements that eliminate joint property formation when money laundering crimes occur, focusing on the tension between contractual property separation and criminal asset confiscation. Using normative legal research methods with statutory and case analysis approaches, this study analyzes Indonesian marriage law, anti-money laundering legislation, and judicial decisions, specifically Decision Number 70/Pid.Sus-TPK/2024/PN.Jkt.Pst and its appellate decision Number 1/Pid.Sus-TPK/2025/PT DKI. The findings reveal that while marriage agreements provide legal protection for individual property rights, courts apply the "follow the money" principle to trace and confiscate assets regardless of formal ownership structures when money laundering is suspected. Marriage agreements are not recognized as absolute barriers to asset seizure if spouses cannot prove the lawful origin of their property or if evidence indicates they benefited from proceeds of crime. This study contributes to understanding the limitations of marriage agreements as protective instruments in criminal proceedings and demonstrates that substantive proof of asset origins supersedes formal contractual arrangements in money laundering cases. The research recommends that spouses executing marriage agreements maintain meticulous documentation of property origins, including purchase receipts, income records, and endorsement contracts, to avoid unjustified confiscation while acknowledging that legitimate law enforcement interests in recovering proceeds of crime may override private contractual protections.